Lateral heterostructures and one-dimensional interfaces in 2D transition metal dichalcogenides. (21st March 2019) - Ávalos-Ovando, O; Mastrogiuseppe, D; Ulloa, S E
Abstract: The growth and exfoliation of two-dimensional (2D) materials have led to the creation of edges and novel interfacial states at the juncture between crystals with different composition or phases. These hybrid heterostructures (HSs) can be built as vertical van der Waals stacks, resulting in a 2D interface, or as stitched adjacent monolayer crystals, resulting in one-dimensional (1D) interfaces. Although most attention has been focused on vertical HSs, increasing theoretical and experimental interest in 1D interfaces is evident. In-plane interfacial states between different 2D materials inherit properties from both crystals, giving rise to robust states with unique 1D non-parabolic dispersion and strong spin–orbit effects. With such unique characteristics, these states provide an exciting platform for realizing 1D physics. Here, we review and discuss advances in 1D heterojunctions, with emphasis on theoretical approaches for describing those between semiconducting transition metal dichalcogenides MX 2 (with M   =  Mo, W and X   =  S, Se, Te), and how the interfacial states can be characterized and utilized. We also address how the interfaces depend on edge geometries (such as zigzag and armchair) or strain, as lattice parameters differ across the interface, and how these features affect excitonic/optical response. This review is intended to serve as a resource for promoting theoretical and experimental studies in this rapidly evolving field.